Surveys at Bagan Percut, Sumatra, reveal its international importance to migratory shorebirds and breeding herons - Putra, Chairunas A; Hikmatullah, Desy; Prawiradilaga, Dewi M; Harris, J. Berton C (KUKILA, 2015)
The Bagan Percut region of north-eastern Sumatra, Indonesia, is becoming well known for its large concentrations of migratory shorebirds. From January to June 2011 we made monthly counts of shorebirds and waterbirds at four mudflats and one heron rookery. Fifty-one species were recorded, including 35 migratory species, and eight breeding species in the rookery. We counted 20,114 migratory shorebirds (mudflats) and 45,648 breeding waterbirds (rookery) over six months of surveys. We observed >1% of the East Asian-Australasian flyway population of five species of migratory shorebirds: Nordmann’s Greenshank Tringa guttifer (globally Endangered), Lesser Sand Plover Charadrius mongolus, Pacific Golden Plover Pluvialis fulva, Eurasian Curlew Numenius arquata, and Ruddy Turnstone Arenaria interpres. Our results support the work of others that indicate that Bagan Percut is an important habitat for wintering, migrating, and summering shorebirds. We recommend that Bagan Percut be added to the East Asian-Australasian Flyway Partnership list of internationally important wetlands because the area meets all three criteria for inclusion.